Influence of walnut trees (Juglans regia L.) on soil urease activity - Kot, Mirosława; Bucki, Marek; Olech, Zofia (Polish Journal of Agronomy, 2020)
Soil urease is an enzyme catalyzing the hydrolysis of urea. The activity of the enzyme influences the content of ammonia ions in soil and thereby the fertility of the soil. 5-hydroxy-1,4-naphthalenedione (juglone) is a compound which inhibits urease. The compound is released by trees of the Juglandaceae family (walnut trees) and is present in their leaves, roots, husks and fruits. The aim of the study was to determine the effect of walnut trees on the activity of soil urease. Urease activity was determined in the soil beneath the tree crown and beyond. It has been shown that soil urease activity is higher in the area outside of the tree crown than beneath it. Less active urease slows down the natural nitrogen cycle resulting in decreased soil fertility. The lower soil fertility slows the growth of plants. This shows non direct influence of juglone on the growth of plants in the vicinity of walnut trees. The greatest difference in urease activity beneath and beyond the crown was observed near the oldest tree. This indicates that the development of the crown and root system increases the amount of secreted juglone. Soil active acidity and exchange acidity were measured. The study did not show a significant correlation between soil urease activity and soil acidity in the observed pH range.